Indonesia–English Translation of Idiomatic Expressions in The Novel This Earth of Mankind - Astri Dwi Floranti; Yasir Mubarok (Buletin Al-Turas, 2020)
The study investigated Indonesia–English translation of idiomatic expressions, focusing on the idioms, in one of Indonesian best seller fiction story, Bumi Manusia  which was translated into English as This Earth of Mankind. The study identified the types of the translation strategies by the translators to reproduce the idioms from SL in TL and the accuracy level of their latest meanings in TL. Qualitative research method in the design of content analysis was employed. The result portrayed that the most dominant strategy employed by the translator was paraphrasing. The translator reproduced the original meaning of the idioms by selecting common vocabularies in TL (non-idiom forms) that shared identical meanings with the idioms in SL or explaining the idioms in SL at longer statements in TL. The other idioms could be translated equivalently in the form of idioms in TL, but they were realized in different lexical words from SL. Furthermore, most of idioms achieved equivalent meanings, but decreased meanings were unavoidable. Thus, it can be seen that the translator attempted to recreate the similar equivalence meaning of the idioms from SL through paraphrasing strategy instead of omitting the idioms in TL. Most of the translated idioms could be reproduced similarly with the original idioms.